PENGEMBANGAN VIDEO PEMBELAJARAN SEBAGAI SUMBER BELAJAR MANDIRI SELAMA PANDEMI COVID-19 - Fifit Fitriansyah (Jurnal Pendidikan dan Kebudayaan Missio, 2021)
The condition of the Covid-19 pandemic has made learning that was originally face-to-face turning online, of course, brings new problems in learning, especially in practical learning. One of the efforts was to fulfill needs learning is through the use of media who had played a role as a tool or an intermediary that support the teaching process .In relation to this matter one of the media learning that can be used is a video. This study aims to develop PNPR 2 learning videos to facilitate learning by producing various independent learning resources in the form of instructional videos that can be used according to learning needs. The research method used is Research and Development (R & D) using the Derek Rowntree product development model with three stages, namely: a) the planning stage; b) the development stage (development); c) the evaluation stage (formative evaluation). Product effectiveness testing is carried out by providing advice and input from colleagues (one to one person). The results of this study indicate that (1) the development of instructional videos that was much as 87% is considered clear and effective for use in the learning process more broadly. Meanwhile, to measure the effectiveness of using PNPR 2 learning videos is to conduct performance tests on full stop, as such it was found that the percentage of student learning outcomes after using PNPR 2 learning videos was that 89% of students to display good performance, 11 % poor practice well or said wrong. Thus the PNPR 2 learning video is considered effective to be used in the learning process.